The Sistem IoT Untuk Monitoring Suhu dan Pengaturan Kelembaban Penetasan Telur Penyu - Nurmahsya, Guruh Khedar; Misbahuddin, Misbahuddin; Paniran, Paniran (Journal of Computer System and Informatics (JoSYC), 2024)
Turtles are endangered and protected animals today, the turtle population is declining all the time due to various factors, including climate change and global warming. Turtles are TSD or Temperature dependent Sex Determination animals with the development of their embryos dependent on temperature and humidity which requires moisture content in the nest during the incubation period. As a conservation effort carried out at the Kuranji Dalang Conservation, West Lombok aims to design an Internet of Things (IoT)-based system made to monitor temperature and regulate sand moisture. This tool is designed to monitor the environmental temperature in the sand area if the optimum temperature at hatching is 25°C-33 °C using DHT11, and regulates the humidity of the nest sand by 21%-40% using a soil moisture sensor. Eggs during the incubation period of turtles with a nest temperature of 25°C-29 °C will become male hatchlings, while the nest temperature of 29 °C-33 °C will become female hatchlings. This system is controlled using an ESP32 NodeMCU microcontroller whose data is transmitted through a blynk that can be monitored remotely, the tests that have been carried out are able to monitor an average temperature of 29-30 °C, in addition to being able to regulate an average humidity of 27.93. With a water pump watering with a duration of 12 seconds in the morning, 25 seconds in the afternoon and 17 seconds in the afternoon when the sand is dry with a predetermined humidity of 21%-40%.